The ways of God : how God reveals himself before a watching world - Blackaby, Henry T., 1935-; Edgemon, Roy T. (Nashville, Tenn. : Broadman & Holman, 2000)
Join teacher and best-selling author Henry Blackaby as he shares the ways of God, which are definitely not the ways of the world. The ways of God require faith and obedience, which lead to His fullness of life.
God's ways are not our ways -- The ways of God are love -- The ways of God are sovereign -- The ways of God are holy -- The ways of God are true -- The ways of God are eternal.
Keywords: Providence and government of God -- Christianity; God (Christianity) -- Attributes; Christian life; Christian life; God (Christianity) -- Attributes; Providence and government of God -- Christianity